Bone Cement and Associated Failures with Total Hip Joint Replacement: A Review Study - I.Aldebs, Alyaa; . A. Abdulameer, Hanaa; A. Ali, Saba (International Journal of Psychosocial Rehabilitation, 2021)
Bone cement is considered the gold standard in orthopedic surgeries for hip implant fixation, providing stability and enhancing implant longevity. Polymethyl methacrylate (PMMA) bone cement is the most widely used biomaterial in implant arthroplasty. It functions as an adhesive, filling the space between the prosthetic joint and the surrounding bone tissue, allowing patients to perform daily activities independently by providing the necessary strength.The goal of this review is to highlight the current state of cementing techniques in total hip replacement surgery. It discusses the mechanical and physiological properties of bone cement, the cementing techniques used, and the main challenges encountered during hip joint implant surgeries. Aseptic loosening is one of the most common causes of failure in cemented hip implants. This failure is attributed to mechanical issues such as degradation of the cement mantle, agglomeration of radiopacifier particles, fatigue crack initiation, and mechanical loosening due to porosity. Understanding these factors can lead to improved cement formulations, potentially increasing the survival rate of cemented implants.